MATERNIDAD Y VACACIONES EN EL ÁMBITO EUROPEO: EL ASUNTO MERINO - Gallego Moya, Fermín (Revista de Derecho, 2020)
In the analysed judgement, a community milestone in the application of the right to effective equality between women and men, the CJEU recognises the worker, whose holiday period, arranged in advance, coincided with her maternity leave, the right to her enjoyment in a subsequent period, taking into consideration the different purpose between the two situations and a material interpretation of the principle of equality and non-discrimination. The repercussion of this community pronouncement, in the jurisprudential and legislative fields, has been very relevant, with the doctrine on holidays being found in a permanent process of reconstruction.